Design of Corrugated Cardboard Product Delivery Allocation Model by Considering Heterogeneous Fleet and Multi Product - Zuya, Novika; Sembiring, Meilita Tryana; Nazaruddin (Jurnal Sistem Teknik Industri, 2025)
Manually planning truck usage by estimating the right fleet selection, as well as considering capacity, delivery zones, and variations in demand, often results in inaccuracies. This inaccuracy has an impact on fleet utilization that is not yet optimal, characterized by low capacity used for each trip and the presence of fleets that are idle at certain times. Apart from that, inappropriate delivery allocation planning and less than optimal fleet utilization also affect delivery timeliness. This research proposes a delivery allocation model to solve the Capacitated Vehicle Routing Problem (CVRP) problem using a Genetic Algorithm (GA) implemented within the Multi-Objective Evolutionary Algorithm (MOEA) Framework. The model is designed to address CVRP by considering heterogeneous vehicle fleets, product variability, and diverse delivery destinations. The chromosome representation in the model describes the sequence of customer visits by the available fleet, while the fitness function is focused on minimizing the total traveled distance in order to maximize the efficiency of vehicle capacity utilization. Based on test results at PT In addition, this model succeeded in reducing the number of fleets used by up to 50%.